Multivariate Data Analysis and Social Media: a Contribution to Infodemic Management Optimization Strategy - Hribar, Susanah Bernardo da Silva Diniz (2023)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Information Analysis and Management